Peningkatan Kinerja Karyawan melalui Lingkungan Kerja dan Kepuasan Kerja pada Karyawan di PT AkuamarinIndonesia Raya - Aay Umanuari; Noveria Susijawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of the work environment and job satisfaction on employee performance at PT Akuamarin Indonesia Raya. The research method used is a quantitative method with an explanatory approach. The study population consisted of 154 employees, and the entire population was sampled using a census technique (saturated sampling). Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression analysis with the help of SPSS. The results show that the work environment has a positive and significant effect on employee performance, with a calculated t-value of 7.881 and a regression coefficient of 0.503. Job satisfaction also has a positive and significant effect on employee performance, with a calculated t-value of 5.311 and a regression coefficient of 0.549. Simultaneously, the work environment and job satisfaction have a positive and significant effect on employee performance, with an F-value of 272.279 and a significance level <0.001. The coefficient of determination (R²) of 0.783 indicates that 78.3% of the variation in employee performance can be explained by the work environment and job satisfaction. The conclusion of this study indicates that the work environment and job satisfaction are important factors that can improve employee performance, with the work environment having a more dominant influence than job satisfaction on employees at PT Akuamarin Indonesia Raya. Keywords: Work Environment, Job Satisfaction, Employee Performance, Human Resources